Munchausen Syndrome: An Adolescent Injuring Her Mother and Herself - Gökçen, Cem; Gezer, Nesrin; Karadağ, Mehmet; Özokutan, Bülent H. (European Journal of Therapeutics, 2023)
Munchausen syndrome is characterized by physical symptoms that are produced by the individual to present as an ill person. Patients in this group may present with various symptoms, such as neurological, hematological, and gastrointestinal problems; this is one of the reasons that make it difficult to diagnose. We report a case of a 16-year-old female patient who was admitted to the Pediatric Surgery Clinic after appendectomy due to abdominal pain, bleeding from the umbilicus, and bulging on the operation zone; laboratory tests performed were found to be in the normal range. On continuation of hemorrhage and doubt that it may be the center of bleeding, the wound area was explored in operating room conditions, but no bleeding center was found. On laboratory examination of the blood sample in the umbilical area, it was determined that the blood was incompatible with the patient, and that she obtained the blood from her mother by an injector. The patient was referred to our Child and Adolescent Psychiatry Clinic. It was learned that the patient had been taking care of her mother and also of housework. The child was getting away from difficult life conditions for a time during hospitalization, and her workload was diminishing. These individuals may apply with an acute disease scenario, which are particularly caused by self-injurious behavior, for which reason they may be exposed to invasive diagnostic procedures. Munchausen syndrome is considered when there is absence of underlying organic pathology.